Organic Acids Supplementation in the Diets and Performance of Broiler Chicken - Tomar, Jitendra Singh; Nayak, Sunil; Baghel, R.P.S.; Malapure, C. D.; Govil, Kumar; Thakur, Dinesh (Indian Journal of Animal Nutrition, 2017)
The experiment was designed to evaluate the effects of organic acid supplementation on performance, nutrient digestibility, carcass traits and economics of feeding in broiler chicken. One hundred ninety eight, one day old chicks were randomly divided into 11 dietary treatments, each treatment consisted of 3 replicates with 6 chicks each. Broilers were fed with standard diet to meet the nutrient requirements. In treatment T1, broilerswere fed standard diet without any organic acid supplementation. In treatments T2, T3, T4, T5 and T6 different organic acids viz. acetate, sorbate, propionate, butyrate and lactate were supplemented @ 2% of the diet, respectively. While, in diets T7 to T11 same organic acids were supplemented @ 3% of the diet. Results indicated higher (P